Bawean Tourism: A Hope to Encourage The Local Economy of The Community - Durratun Nashihah; Tjahjanulin Domai; I Gede Eko Putra Sri Sentanu (Sekolah Pascasarjana Universitas Brawijaya, 2021)
Bawean Island is located 130 kilometers north of Java Island with an area of 200 square kilometers and a population of around 107,000. One aspect that needs to be considered on the Bawean island is the welfare of the community. The condition of human resources in Bawean Island is on average uneducated to a high level and with middle to lower economic conditions. Most of the livelihoods of the people of Bawean Island are farming, fishing or migrating abroad. Bawean Island has abundant natural resources, there are beaches, lakes, waterfalls, mountains and small islands, all of these natural objects can be developed into tourist locations. Tourism encourages economic growth in an area because it opens up many business opportunities and jobs that empower people.Â Tourism potential can be seen as a solution to improve the welfare communitiesÂ on Bawean Island. This research focuses on extracting data and analyzing how the tourism sector is able to be a solution for increasing welfare in Bawean Island. The object observed was the development of a tourism village and the parties involved, namely the government and tourism-conscious community groups including empowered communities. This research provides information on the impact of tourism on increasing welfare by looking at the number of creative industry communities and empowered communities.